Kadar Religiusitas Santri Panti Asuhan Keluarga Yatim Muhammadiyah Surakarta Tahun 2015 - Yasin Hadi Pranoto, Akhmad, Dr.sudarno shobron,M.Ag, Dr.Waston,M.Hum (2016)
The teens in Indonesia lately started familiar with the globalization of technology and information. Proven by many internet users, not just the teenagers, parents and children have participated incorporated.Orphanage as an institution which accommodates orphans, piyatu, piyatu orphans and orphans was time to have a role more than just being a shelter but it increases to a formation of a strong Islamic character. Preparing foster children have a good competence religiosity as a power filter of the swift currents of globalization and information technology, which in turn will bring mashlahat and not bring madlarat. These conditions encourage the authors to examine how levels of religiosity students Orphanage Family Yatim Muhammadiyah Surakarta today. The purpose of this study was to determine how the level of religiosity of students Orphanage Family Yatim Muhammadiyah Surakarta. Theoretically, the results of this study would be useful to develop a level of religiosity in PAKYM students and is expected to have more in-depth assessment process produces better religiosity competence. In practical terms, for Orphanage Family Yatim Muhammadiyah Surakarta this study can be used as a basis for improving and developing the quality of care, planting beliefs or morals, and character development of students in social life. This study is also useful for general muhammadiyah is to enrich the data and empirical facts under the auspices of Muhammadiyah orphanage so muhammadiyah could be a community organization that is professional in handling the orphans. The data collected in this study uses questionnaires, interviews, documentation, and observation. The analytical method used is descriptive analytical method. The result showed that level of students religious Orphan Family Orphanage Muhammadiyah Surakarta is in a good category. This is because the value - average 77,90 which is in the interval 78-93, so it shows that the level religious PAKYM students showed a good category.